PELABUHAN REMBANG 1820 -1900(Profil Pelabuhan Kecil Dan Pengaruhnya Terhadap Perkembangan Ekonomi Wilayah Rembang) The Port of Rembang 1820-1990: A Profile of a Small Port and Its Inflluence on Rembang Regency Ekonomical - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
Rembang is located on the north coast of Java which inherited the old maritime tradition with its great port. In some sources, Rembang is often called as a port area